2016
DOI: 10.1038/srep32173
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-17 Pathways in Immune Privilege: A RNA Deep Sequencing Analysis of the Mice Testis Exposure to Fluoride

Abstract: We sequenced RNA transcripts from the testicles of healthy male mice, divided into a control group with distilled water and two experimental groups with 50 and 100 mg/l NaF in drinking water for 56 days. Bowtie/Tophat were used to align 50-bp paired-end reads into transcripts, Cufflinks to measure the relative abundance of each transcript and IPA to analyze RNA-Sequencing data. In the 100 mg/l NaF-treated group, four pathways related to IL-17, TGF-β and other cellular growth factor pathways were overexpressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Interestingly, IL-17RC was signi cantly increased in the testis of WT uorosis mice, but the content of IL-17RA was not signi cant and this needs further study. Consistented with previous results, the IL-6, IL-23, IL-1β and TGF-β were increased in the testis when the WT mice exposed 50 mg/L NaF [6]. There have a investigation also indicated that the mRNA levels of TGF-β, IL-1β, IL-6, and IL-21 up-regulated intestis after F exposure [32].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, IL-17RC was signi cantly increased in the testis of WT uorosis mice, but the content of IL-17RA was not signi cant and this needs further study. Consistented with previous results, the IL-6, IL-23, IL-1β and TGF-β were increased in the testis when the WT mice exposed 50 mg/L NaF [6]. There have a investigation also indicated that the mRNA levels of TGF-β, IL-1β, IL-6, and IL-21 up-regulated intestis after F exposure [32].…”
Section: Discussionsupporting
confidence: 87%
“…Research at the cellular level found excessive uoride intake can amplify apoptosis, autophagy and even death of germ cells [5]. Intriguingly, using the sequenced RNA transcripts from the testicles of healthy and uorosis male mice in our study, we found four pathways related to IL-17A signaling that were overexpressed in the testes of uorosis male mice [6]. This indicates that IL-17A may be the pivotal regulator in the process of excessive uoride-induced testicular damage in mice.…”
Section: Introductionsupporting
confidence: 50%
“…The testis is considered as an immune privileged organ, nevertheless, toxic agents and inflammation may overwhelm immune suppressor mechanisms resulting in autoimmune reactions against spermatic antigens. Consequently, this may result in aspermatogenesis and infertility [51]. In the present study, sleep deprivation resulted in significant rise in IL-6 and Il-17, which could be countered by the treatment with vitamin C. Nevertheless, some cytokines such as IL-1, and IL-6 can also produced by Leydig and Sertoli cells [25].…”
Section: Discussionmentioning
confidence: 45%
“…Excess IL-17 is commonly associated with different types of inflammation, and as for our study, IL-17 serum levels were elevated in the sleep deprived male rats. It has been reported previously that LI-17 and its signaling pathway were highly expressed in mice testis exposed to high fluoride [51]. IL-17 was found to be critically involved in male patients with azoospermic testis with chronic inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…All unigenes were compared with 4 databases: Nr, COG, KEGG, and Swiss-Prot by BLASTX with cutoff E-value of 10 −5 . Significant differences in gene expression were evaluated using a threshold value of absolute log 2 -fold change >1 with a FDR <0.05 and P < 0.05 39 , 40 . The Pearson’s correlation coefficient between protein and mRNA data was calculated, and scatter plots for FON and FONM expression ratios were created.…”
Section: Methodsmentioning
confidence: 99%